Long Term Evaluation of Anterior Primary Resin Crown in Pediatric Patient - Annisa Listya Paramita; Sandy Aditya Susilo (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2017)
Background: Nursing bottle carries is a problematic condition in children. On one side, parents try to supply enough nutrition to their children, though on the other side this night- time bottle feeding habit might cause negative effect on the childrens dental health. Esthetic dental treatment on children have improved greatly over the past few years, as parents expect an almost-complete restoration of their child’s dental condition. The alternatives for pediatrics esthetic dental restoration may depend on the cooperativeness and habit of the child themselves, while also taking the child’s development into consideration. Aim: to report evaluation of aesthetic restoration on primary teeth. Case: A 4 year-old female child was presented by her parents, with damaged four anterior teeth, which made her uncomfortable especially on feeding due to the sharp edges. From history taking we found a night-time bottle-feeding habit, which usually occurred until patient was asleep. Case Management: restoration of the four primary incisive teeth was performed using a resin composite crown. Outcome of the treatment was evaluated until the primary teeth exfoliateand permanent teeth arise. Conclusion: cooperation between patient, parents, and dentist is important in the dental restorative treatment on paediatric patient. Moreover, a good communication with parents is encouraged, especially on follow-up schedule, treatment cost, success rate and possibility of treatment failure is also encouraged. Staged evaluation is needed due to the natural substitution of the primary teeth by permanent teeth, besides the development process of the jaws.